A pleasant coach journey across the political frontier: Public art and suburban dissensus. Issue 2 (1st December 2019) - Cross, David; Bishop, Cameron
'Six Moments in Kingston Town' was an art project developed by the Public Art Commission in May 2019 that sought to collectively speak to the diverse cultures and shared histories of the City of Kingston, south of Melbourne. A series of leading Australian artists were commissioned to work with local community groups to develop projects that spoke to the complex, rich and interwoven social fabrics of this region, concentrating on the period of the mid-1970s to early 1980s. Using as key case studies events such as the election of Moorabbin's first female councillor in 1976, a selection of nationally famous political protests in 1982, and the disappearance of aviator Fred Valentich who flew out from Moorabbin airport in 1978 never to be seen again, the project sought to highlight hidden or obscured historical moments that impacted well beyond the Kingston region. This text examines how curatorial practice via the commissioning of a series of iterative, place-specific, temporary projects can serve to nurture resilient communities while showcasing adventurous, challenging contemporary art. In picking up on local gestures, materials and events that clearly resonate with our contemporary milieu, we bring into question art's repeated teleology ‐ one that eschews resistance in favour of its own disappearance into a kind of utopic consensus, where politics, art, culture and the economy fuse into a life of communal accord. In this article, we argue that the making of public artworks as dissensus serves to resist the collapse of art into life and, therefore, the danger that, with the disappearance of art, politics is doomed as well. As the article progresses, we pick up on a number of theoretical threads that present the works as ruptures in our conventional approaches to these sites and their histories.